2003
DOI: 10.1515/bc.2003.147
|View full text |Cite
|
Sign up to set email alerts
|

Kinin-B1 Receptors in Ischaemia-Induced Pancreatitis: Functional Importance and Cellular Localisation

Abstract: receptor protein was confirmed at the same sites. In conclusion, we have demonstrated the up-regulation of the pancreatic acinar cell kinin-B1 receptors during ischaemia/reperfusion. The novel functional finding was that antagonism of the kinin-B1 receptors decreased the survival rate in an experimental model of pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…[52][53][54] Activation of the kinin-kallikrein system is observed in pancreatitis and causes the vascular effects associated with the disease. 55,56 Inhibition of bradykinin action is used as a mode of therapy for pancreatitis patients. [56][57][58][59][60] Vitronectin is also consistent with hemolysis and pancreatitis because of its role as a complement and cytolysis inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54] Activation of the kinin-kallikrein system is observed in pancreatitis and causes the vascular effects associated with the disease. 55,56 Inhibition of bradykinin action is used as a mode of therapy for pancreatitis patients. [56][57][58][59][60] Vitronectin is also consistent with hemolysis and pancreatitis because of its role as a complement and cytolysis inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Inhibition of bradykinin action is used as a mode of therapy for pancreatitis patients. [56][57][58][59][60] Vitronectin is also consistent with hemolysis and pancreatitis because of its role as a complement and cytolysis inhibitor. 61,62 Each of these proteins plays a role in pancreatic inflammation and the corresponding host response.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, either pharmacological blocking with selective B 1 antagonist [Leu 8 ]‐des‐Arg 9 ‐BK or gene deletion of B 1 receptors largely diminishes the infarction's extension, an effect that further reinforces the relevance of B 1 receptors under these conditions. Kuebler et al . (2003) have affirmed that B 1 receptors also seem relevant in the ischaemia–reperfusion of rat pancreas.…”
Section: The B1 Receptor and Its Role In Development And Maintenance mentioning
confidence: 99%
“…The authors have demonstrated, by means of binding studies, that B 1 receptor expression is augmented by about 22‐fold after pancreatic ischaemia–reperfusion injury. They have also shown that the B 1 receptor antagonist CP‐0298 (alone or in combination with the B 2 antagonist CP‐0597) significantly reduces the number of adherent leukocytes in postcapillary venules ( Kuebler et al ., 2003 ). Another recent contribution has demonstrated that intestinal ischaemia–reperfusion injury results in a striking increase of B 1 receptor expression in rats ( Souza et al ., 2004 ).…”
Section: The B1 Receptor and Its Role In Development And Maintenance mentioning
confidence: 99%
“…Much evidence suggests that the integrity of vascular endothelium is an important factor for the development and maintenance of pancreatic islet function (Konstantinova and Lammert, 2004). Accordingly, the expression of kinin B 1 receptor has been described in pancreas (Chai et al, 1996) and it has been demonstrated that this receptor mediates leukocyte adherence in capillary venules in pancreatic vessels (Kuebler et al, 2003) and controls plasma extravasation in pancreatitis in streptozotocintreated mice (Simard et al, 2002;Lawson et al, 2005). Recently, we generated and characterized kinin B 1 receptor knockout mice (B 1 -/-), which were shown to be fertile, normotensive, hypoalgesic and less responsive to lipopolysaccharide (LPS)-induced hypotension (Pesquero et al, 2000).…”
Section: Introductionmentioning
confidence: 99%